1989
DOI: 10.1056/nejm198903233201203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Marijuana and Cocaine Use on Fetal Growth

Abstract: To investigate the effects on infants of the use of marijuana and cocaine during pregnancy and to compare the importance of urine assays with that of interviews in ascertaining drug use, we prospectively studied 1226 mothers, recruited from a general prenatal clinic, and their infants. On the basis of either interviews or urine assays conducted prenatally or post partum, 27 percent of the subjects had used marijuana during pregnancy and 18 percent had used cocaine. When only positive urine assays were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
154
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 770 publications
(160 citation statements)
references
References 24 publications
5
154
0
1
Order By: Relevance
“…Heavier prenatal marijuana exposure was associated with lower height z score but higher weight for height z score. While few long-term studies of growth outcomes of prenatally marijuanaexposed children exist, data collected at birth indicate a significantly lower birth length [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavier prenatal marijuana exposure was associated with lower height z score but higher weight for height z score. While few long-term studies of growth outcomes of prenatally marijuanaexposed children exist, data collected at birth indicate a significantly lower birth length [41].…”
Section: Discussionmentioning
confidence: 99%
“…Related to fetal growth however, there are consistent findings indicating that after consideration of a large number of covariates, prenatal cocaine exposure has specific effects on infant birth parameters including head circumference, weight and length [4,5,9,11,12,31,37,41]. Growth deficits are believed to result from poor maternal nutrition, restricted placental blood flow or some other unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the active ingredient of cannabis, tetrahydrocannabinol, crosses the placental barrier and directly affects the fetus. Persistent use of cannabis may result in decreased uteroplacental perfusion and intrauterine fetal growth restriction (4). Previous research linking antenatal cannabis use and adverse pregnancy outcomes has been inconclusive (5).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] One study concluded that exposure to cocaine and marijuana did not alter neonatal body proportionality. 4 Another study found that head circumferences of cocaine exposed newborns were relatively smaller than would be expected at a given birth weight.…”
mentioning
confidence: 99%